Analisis Kinerja Pegawai dalam Pelayanan Publik di UPTD Pengujian Kendaraan Bermotor Kota Kupang - Juliaty Doko E. Eddo Huky; Marthina Raga Lay; David Wilfrid Rihi; Yani Handani Seran (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines employee performance in public services at the Motor Vehicle Testing Unit (UPTD Pengujian Kendaraan Bermotor) of Kupang City. The study aims to analyze employee performance using the public organizational performance indicators proposed by Dwiyanto, namely productivity, service quality, responsiveness, and responsibility. A qualitative descriptive approach was employed through observations, in-depth interviews, and document analysis, while the data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that employee performance is generally categorized as good; however, it has not yet reached an optimal level. Service quality, responsiveness, and responsibility have been implemented in accordance with the established Standard Operating Procedures (SOP), as reflected in accurate vehicle inspections, effective communication with service users, and compliance with technical regulations. Nevertheless, productivity remains constrained by the imbalance between the number of vehicle inspectors and the volume of vehicles tested, resulting in service delays beyond the established standards. In addition, limited technical training, insufficient maintenance of testing equipment, and inadequate supporting facilities affect service effectiveness. The study concludes that improving public service performance requires strengthening institutional capacity, enhancing human resource competencies, and ensuring the sustainability of supporting infrastructure to provide effective, efficient, and accountable vehicle testing services.